2007
DOI: 10.1007/s10661-007-9783-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Polish cigarettes contamination with cadmium and lead, and exposure to these metals via smoking

Abstract: To estimate exposure to cadmium (Cd) and lead (Pb) through cigarette smoking, the concentrations of both metals in the blood or/and urine of smokers (20 cigarettes or more per day for 10 years or longer) and their non-smoking counterparts inhabiting an environmentally unpolluted area (Bialystok, Poland) were evaluated, as well as Cd and Pb contents in the cigarette brands (produced in Poland) smoked by the participants, including intact cigarettes, pre-smoking (tobacco, paper and filter) and post-smoking (butt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 31 publications
7
73
2
4
Order By: Relevance
“…Galazyn-Sidorczuk et al (2008) evaluated levels of lead in several brands of cigarette, found concentrations of lead ranging from 0.69 ± 0.07 μg/cigarette and set the amount of Pb inhaled could reach 0.208 to 1.033 μg. Schroijen et al (2008) in studies of exposure to pollutants with adolescents living in areas around waste incinerators, showed increased body burden of several environmental contaminants, among them Pb, corroborating the findings of this study that the exposure to smoke from the burning of household waste is an important factor for the exposure of children to the metal, besides the possibility of exposure to other contaminants present in the smoke generated during this waste disposal habit.…”
Section: Discussionmentioning
confidence: 99%
“…Galazyn-Sidorczuk et al (2008) evaluated levels of lead in several brands of cigarette, found concentrations of lead ranging from 0.69 ± 0.07 μg/cigarette and set the amount of Pb inhaled could reach 0.208 to 1.033 μg. Schroijen et al (2008) in studies of exposure to pollutants with adolescents living in areas around waste incinerators, showed increased body burden of several environmental contaminants, among them Pb, corroborating the findings of this study that the exposure to smoke from the burning of household waste is an important factor for the exposure of children to the metal, besides the possibility of exposure to other contaminants present in the smoke generated during this waste disposal habit.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smokers are exposed to significant amounts of cadmium (Cd) and lead (Pb) (54), which accumulate in kidney tissue more than in any other organ and are toxic at very low dosages (55). According to studies from Egypt, smoking has toxic effects on tubular cells, which are synergistic to occupational Pb (56), mercury (57), and silica (58) exposure.…”
Section: Nonhemodynamic Mechanisms As Potential Mediators Of Smoking-mentioning
confidence: 99%
“…It is observed that contents of lead (7)(8)(9) and arsenic (10-12) in biological samples of human population are much higher in smokers than those in non-smokers.…”
Section: Introductionmentioning
confidence: 99%